Quantifying farmers' preferences for cropping systems intensification: A choice experiment approach applied in coastal Bangladesh's risk prone farming systems - Aravindakshan, Sreejith; Krupnik, Timothy J.; Amjath-Babu, TS; Speelman, Stijn; Tur-Cardona, Juan; Tittonell, Pablo A.; Groot, Jeroen C.J. (Elsevier, 2021)
CONTEXT Sustainable intensification (SI) is envisioned as an effective strategy for developing countries to increase farm productivity while reducing negative environmental and social externalities. The development of regionally appropriate SI options however requires accounting for the knowledge and preferences of key stakeholders. In Bangladesh, the Government has requested international donors to support the development of dry season rice expansion in the coastal region. Policies however tend to be made without adequate study of farmers' preferences and ambitions; this can render crop intensification efforts ineffective. Understanding farmers' preferences for alternative crops and crop management practices are therefore crucial for success where agricultural development investments aim at incorporating the principles of SI.